2019
DOI: 10.1002/mmce.21676
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐band and wideband omnidirectional circularly polarized antenna based on VO2

Abstract: In this article, a dual‐band and wideband omnidirectional circularly polarized (CP) antenna based on the vanadium dioxide (VO2) is investigated. The operating bandwidth of such an antenna can be regulated by altering the outside temperature (T), which is attained by the insulator‐metal transition of VO2. The omnidirectional CP antenna is based on a loop antenna‐dipole model, which is composed of four tilted metal and VO2 resonant units that are loaded around a cuboid and a feeding network for broadening bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In recent years, a variety of tunable omnidirectional circularly polarized (CP) antenna have been reported using VO 2 . For example, Guo-Biao Liu et al [127] reported dual band and wideband omnidirectional CP antenna which shown a 10-dB impedance bandwidth of 45.7% (1.67-2.66 GHz) and a 3-dB AR bandwidth of 40% (1.9-2.85 GHz), when the VO 2 was thermally elevated at 50 • C (state I). When T = 80 • C (State II), the omnidirectional CP antenna operates at a lower frequency band, with a 10-dB impedance bandwidth of 13.8% (1.62-1.86 GHz), and a 3-dB AR bandwidth of 21.8% (1.68-2.09 GHz).…”
Section: Reconfigurable Antennasmentioning
confidence: 99%
“…In recent years, a variety of tunable omnidirectional circularly polarized (CP) antenna have been reported using VO 2 . For example, Guo-Biao Liu et al [127] reported dual band and wideband omnidirectional CP antenna which shown a 10-dB impedance bandwidth of 45.7% (1.67-2.66 GHz) and a 3-dB AR bandwidth of 40% (1.9-2.85 GHz), when the VO 2 was thermally elevated at 50 • C (state I). When T = 80 • C (State II), the omnidirectional CP antenna operates at a lower frequency band, with a 10-dB impedance bandwidth of 13.8% (1.62-1.86 GHz), and a 3-dB AR bandwidth of 21.8% (1.68-2.09 GHz).…”
Section: Reconfigurable Antennasmentioning
confidence: 99%
“…The operational bands under consideration for 5G mobile networks include 28 GHz, 38 GHz, 60 GHz, and 70 GHz. On the other hand, the 28 GHz and 38 GHz bands are useful for cellular networks, but operating on higher frequency bands would pose challenges to the antenna-configuration mobile communication systems [ 5 , 6 ]. The antenna is one of the crucial components in the transmission link of the future 5G network.…”
Section: Introductionmentioning
confidence: 99%